Dissociation rate, fluorescence and Infrared radiative cooling rates of Naphthalene studied in electrostatic storage Miniring. (July 2015) - Ortega, C; Kono, N; Ji, M; Brédy, R; Bernard, J; Joblin, C; Cassimi, A; Ngono-ravache, Y; Chen, L; Martin, S
Synopsis: We report studies on fluorescence and Infra Red (IR) radiative cooling rates of naphtalene cation for a large time range (40ms). The dissociation rates versus internal energy have been estimated in a large energy range to reproduce the measured emitted neutral yield of the hot naphthalene.